(untitled) (IF-Sophia: revista eletrônica de investigações Filosófica, Científica e Tecnológica, 2017)
The article presents the results of the studies carried out by the author on the appropriation that the philosopher Karl R. Popper, during his life, realized of the theses and behavior of some pre-Socratics. The thinker under study in the article is Anaximander of Miletus, son-in-law and countryman of Thales, the first critical and revisionist rationalist thinker, creator of reason as a rational discursive mode. In this sense, the article aims to present how Anaximander gave continuity to the pedagogical procedures of Thales and extraordinarily deepened the consequences of the critical revisionism of the School of Miletus on the works of Homer and especially those of Hesiod, inaugurating a new way of representing the cosmos the phýsis and the human adventure on Earth, considered by the ancients to be "our home".